Mathematical modeling for the description of drying kinetics of pineapple bark - Leite, Daniela Dantas de Farias (2017)
Brazil is the second largest producer of pineapple in the world. Pulp is the part of the fruit that is normally consumed, whereas the stalk and the bark are considered waste of it’s processing, not being properly utilized by the industries. The objective of this work was to dehydrate the pineapple peel in the form of slices with a length of 15 cm and a width of 8 cm in an oven with forced air circulation at temperatures of 75 and 85 °C and adjust the mathematical models of Henderson and Pabis, Page, Thompson, Diffusion Approximation, Midilli and Two Terms to the experimental data. The coefficient of determination, the mean square deviation and the random distribution of the residuals were used as the criterion for evaluating the adjustment of the mathematical models. The pineapple bark with initial water content of 87.73% b.u had a final water content of 10.67% b.u at 75 °C and 9.05% at 85 °C, with an average reduction of 88, 76% of the initial water content of the study material. It was found that samples submitted to dewatering at 75 °C required a longer time to reach the equilibrium water content compared to dehydrated samples at a temperature of 85 °C. Among the models studied, the Page of diffusion approximation and Midilli presented the highest coefficients of determination (R²> 0.998) and the smallest mean squared deviations (DQM <0.02), however, the Page model was The only one with random distribution of the residues at all temperatures studied, resulting in the best fit to the experimental data of pineapple bark drying.